2017
DOI: 10.1155/2017/4934108
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Practices of the Iranian Population regarding Skin Cancers: A Literature Review

Abstract: Despite being preventable, more than 15% of all cancer cases in Iran occur in the skin, making them the most commonly diagnosed malignancy in the country. The purpose of this study is to gain an insight into the current skin cancer related knowledge, attitudes, beliefs, and practices among the Iranian population. A systematic computer based literature search was conducted using databases for articles published through April 2017. Research studies included those that measured skin cancer or sun protection relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…16 Moreover, a study in Peru noted that women are more knowledgeable about sun protection than men (P 0.001), 17 a study carried out in Iran also concluded the same finding. 18 The current findings state that individuals above the age of 40 use sunscreens with higher SPF levels as compared to the other age groups. This is further supported by an affirmation that adults of older age were more likely to undertake preventative measures to protect themselves from harmful sun exposure.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…16 Moreover, a study in Peru noted that women are more knowledgeable about sun protection than men (P 0.001), 17 a study carried out in Iran also concluded the same finding. 18 The current findings state that individuals above the age of 40 use sunscreens with higher SPF levels as compared to the other age groups. This is further supported by an affirmation that adults of older age were more likely to undertake preventative measures to protect themselves from harmful sun exposure.…”
Section: Discussionmentioning
confidence: 54%
“…This is further supported by an affirmation that adults of older age were more likely to undertake preventative measures to protect themselves from harmful sun exposure. 12,13,15 The present results revealed that 94.7% of female undergraduates use sunscreen, and that 70.2% use the optimal SPF value (15)(16)(17)(18)(19)(20). This signifies that the level of knowledge is higher among female students than others, additionally, they are also more aware of the importance of appropriate sunscreen use.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This cross‐sectional descriptive study was conducted at outpatient pediatric clinics in two different regions of the city (Imam Hossein Children's Hospital and Al‐Zahra Hospital), affiliated with Isfahan University of Medical Sciences, Isfahan, Iran during the summer of 2021. To calculate the sample size while considering a 95% confidence level (zα=1.96 ${z}_{{\rm{\alpha }}}=1.96$), sun‐protective behavior relative frequency of 68.8% (p=0.688 $p=0.688$), according to the study by Nahar et al 22 and a margin of error of 0.06 (d=0.06 $d=0.06$), a sample size (n $n$) of 230 individuals was calculated using n=zα21emp1em(1p)/d2 $n=\left({z}_{{\rm{\alpha }}}^{2}\,p\,(1-p)\right)/{d}^{2}\,$formula. The ethical committee of Isfahan University of Medical Sciences approved this study (Ethical code: IR.MUI.MED.REC.1400.012) in accordance with the latest version of the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional descriptive study was conducted at outpatient pediatric clinics in two different regions of the city (Imam Hossein Children's Hospital and Al-Zahra Hospital), affiliated with Isfahan University of Medical Sciences, Isfahan, Iran during the summer of 2021. To calculate the sample size while considering a 95% confidence level (z = 1.96 α ), sun-protective behavior relative frequency of 68.8% (p = 0.688), according to the study by Nahar et al 22 and a margin of error of 0.06 (d = 0.06), a sample size (n) of 230 individuals was calculated using ( )…”
Section: Study Setting and Selection Criteriamentioning
confidence: 99%